2020
DOI: 10.3390/jcm9082540
|View full text |Cite
|
Sign up to set email alerts
|

Athlete’s Passport: Prevention of Infections, Inflammations, Injuries and Cardiovascular Diseases

Abstract: Laboratory medicine in sports medicine is taking on an ever-greater role in the assessment and monitoring of an athlete’s health condition. The acute or intense exercise practiced by elite athletes can lead to the appearance of infections, inflammations, muscle injuries or cardiovascular disorders, whose diagnosis is not always rapid and efficient, as there is no continuous monitoring of the athlete. The absence of such monitoring can have serious consequences in terms of recovery of the professional athlete. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The beneficial effects of exercise are well known [35]. It has been widely demonstrated that physical exercise can prevent infections [36][37][38], inflammation and delay the onset of cardiovascular and muscular pathologies [39,40]. In this scenario, the practice of physical activity conducted according to the ANTI-COVID-19 rules, and a correct diet, such as Mediterranean Diet can represent a valid tool to combat weight gain and depressive moods that can characterize periods such as those of quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of exercise are well known [35]. It has been widely demonstrated that physical exercise can prevent infections [36][37][38], inflammation and delay the onset of cardiovascular and muscular pathologies [39,40]. In this scenario, the practice of physical activity conducted according to the ANTI-COVID-19 rules, and a correct diet, such as Mediterranean Diet can represent a valid tool to combat weight gain and depressive moods that can characterize periods such as those of quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the urine test could be included in the laboratory analyzes [ 72 ] that would safeguard the athlete’s health and improve physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, because physical activity is relevant for all ages [57,58], moderate exercise combined with satisfactory nutrition are protective factors against cardiovascular disease, muscular-skeletal disorders, obesity, diabetes, cancer, and cellular aging [57][58][59][60][61][62]. Moreover, it is well known that acute or strenuous exercise can lead to muscle injuries, cardiovascular maladaptation, and dysregulation of gut microbiota [63][64][65][66][67][68]. For these and other reasons, appropriate nutrition and adequate supplementation are necessary.…”
Section: Micronutrient Diseases Referencesmentioning
confidence: 99%